2012
DOI: 10.1159/000339597
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Event-Based Methods Using Optical Coherence Tomography and Automated Perimetry to Detect the Progression of Glaucoma in Patients with Open-Angle Glaucoma

Abstract: Background/Aims: To compare event-based methods for estimating the incidence of glaucoma progression using optical coherence tomography (OCT) and automated perimetry and to assess agreement between structural and functional tests for detecting glaucoma progression. Methods: Functional progression of glaucoma was estimated by guided progression analysis (GPA) using a Humphrey field analyzer (HFA), and structural progression was assessed by OCT and defined as the decrease in retinal nerve fiber layer thickness b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Their study showed poor concordance between structural and functional criteria; 22 % of their patients progressed by OCT alone, 9 % by VF-MD alone and 3 % by both VF and OCT. Recently, Lee et al [29] compared event-based analysis on Stratus OCT with progression on visual fields and reported moderate agreement between structural and functional methods of assessment, but they did not mention details of the percentage change or decrease in RNFL thickness observed in their study.…”
Section: Discussionmentioning
confidence: 96%
“…Their study showed poor concordance between structural and functional criteria; 22 % of their patients progressed by OCT alone, 9 % by VF-MD alone and 3 % by both VF and OCT. Recently, Lee et al [29] compared event-based analysis on Stratus OCT with progression on visual fields and reported moderate agreement between structural and functional methods of assessment, but they did not mention details of the percentage change or decrease in RNFL thickness observed in their study.…”
Section: Discussionmentioning
confidence: 96%